2017
DOI: 10.1007/s10802-017-0327-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Parental Emotion Socialization and Children’s Emotion Regulation: The Moderating Role of ADHD Symptomatology

Abstract: Theory and research suggest that parents' reactions to children's emotions play a critical role in teaching children effective emotion regulation (ER) skills, but no studies have directly examined the role that parent emotion socialization plays in the development of ER in children with ADHD. Gaining insight into the causes of impaired ER, particularly in youth with ADHD who are known to have poor ER, has important theoretical and translational significance. The present study is the first to longitudinally exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 76 publications
2
41
1
4
Order By: Relevance
“…This was not entirely unexpected, given that the only other study examining resting RSA as an outcome of supportive parenting found no relation between supportive parenting at age 2 and resting RSA at age 4 (Kennedy et al, 2004), though theory might suggest that supportive parenting would indeed have a main effect on resting capacity for emotion regulation as indexed by RSA (e.g., Beauchaine, 2015;Beauchaine & Zalewski, 2016;Crowell et al, 2014;Shader et al, 2018). However, the literature examining the relation between supportive parenting and RSA reactivity is more equivocal and shows both significant and non-significant associations (e.g., Breaux et al, 2018;Calkins et al, 1998;El-Sheikh, 2005;Gottman et al, 1996;Miller et al, 2013;Perry et al, 2012). One reason for this lack of a direct effect may be due to the developmental period assessed in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not entirely unexpected, given that the only other study examining resting RSA as an outcome of supportive parenting found no relation between supportive parenting at age 2 and resting RSA at age 4 (Kennedy et al, 2004), though theory might suggest that supportive parenting would indeed have a main effect on resting capacity for emotion regulation as indexed by RSA (e.g., Beauchaine, 2015;Beauchaine & Zalewski, 2016;Crowell et al, 2014;Shader et al, 2018). However, the literature examining the relation between supportive parenting and RSA reactivity is more equivocal and shows both significant and non-significant associations (e.g., Breaux et al, 2018;Calkins et al, 1998;El-Sheikh, 2005;Gottman et al, 1996;Miller et al, 2013;Perry et al, 2012). One reason for this lack of a direct effect may be due to the developmental period assessed in the study.…”
Section: Discussionmentioning
confidence: 99%
“…We found only one study that specifically examined associations between parental socialization of emotion and child resting RSA: Kennedy, Rubin, Hastings, and Maisel () did not find that supportive parenting at age 2 significantly predicted resting RSA at age 4. There has been more research examining relations between parental socialization of emotion and RSA reactivity across the developmental spectrum, with parental socialization of emotion showing both significant (e.g., Calkins, Smith, Gill, & Johnson, ; El‐Sheikh, ; Gottman, Katz, & Hooven, ; Miller et al, ) and non‐significant (e.g., Breaux, McQuade, Harvey, & Zakarian, ; Calkins et al, ; Hastings, Klimes‐Dougan, Kendziora, Brand, & Zahn‐Waxler, ; McQuade & Breaux, ; Perry, Calkins, Nelson, Leerkes, & Markovitch, ) associations with RSA reactivity. It is important to note that RSA reactivity, though related to resting RSA, is conceptually distinct.…”
Section: Introductionmentioning
confidence: 99%
“…ES is identified as emotion area-specific parenting and is embedded within general parenting. Emerging evidence shows that parental ES shapes children's emotion repertoire, such as emotion recognition, expression, and regulation (Breaux et al, 2018;Wang et al, 2019), which in turn further impacts children's psychological adjustment and peer relationships (Katz et al, 2012;Jin et al, 2017). For example, helping children identify the cause of angry feelings and teaching children how to address anger-causing problems may provide children with skills they can use next time when playing with a peer, thus potentially buffering their aggression words or behaviors (Nelson and Boyer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Vários estudos correlacionais têm fornecido evidências a respeito das relações entre as reações apoiadoras dos pais e a autorregulação emocional infantil (Meyer et al, 2014;Mirabile, 2015;Han et al, 2015). Adicionalmente, um estudo longitudinal investigou a autorregulação emocional de crianças com e sem sintomas de TDAH e as reações de seus pais e confirmou o poder preditivo das reações apoiadoras (Breaux et al, 2017). Em conjunto, esses achados apoiam a noção de que as reações apoiadoras dos pais às emoções dos filhos facilitam a autorregulação das emoções por parte da criança.…”
unclassified